2016
DOI: 10.1039/c5cp06587a
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for the influence of charge on the adsorption capacity of carbon dioxide on charged fullerenes

Abstract: We show, both experimentally and theoretically, that the adsorption of CO2 is sensitive to charge on a capturing model carbonaceous surface. In the experiment we doped superfluid helium droplets with C60 and CO2 and exposed them to ionising free electrons. Both positively and negatively charged C60(CO2)n(+/-) cluster ion distributions are observed using a high-resolution mass spectrometer and they show remarkable and reproducible anomalies in intensities that are strongly dependent on the charge. The highest a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…92 electric double-layer between a charged carbon surface and different electrolytes 100,101 and by other experimental and theoretical studies indicating the apparent secondary effects of highly polarizing pores/surfaces on CO 2 capture properties. 53,99,102 It is our belief that the combined possibilities of pore size engineering, functionalization of surfaces, the possible applications of electric charge by internal structure motifs or by external stimulus, and especially the stability in the presence of water render carbon-based adsorbents most promising for selective CO 2 capture among the various families of porous materials studied for this purpose in the near future.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%
“…92 electric double-layer between a charged carbon surface and different electrolytes 100,101 and by other experimental and theoretical studies indicating the apparent secondary effects of highly polarizing pores/surfaces on CO 2 capture properties. 53,99,102 It is our belief that the combined possibilities of pore size engineering, functionalization of surfaces, the possible applications of electric charge by internal structure motifs or by external stimulus, and especially the stability in the presence of water render carbon-based adsorbents most promising for selective CO 2 capture among the various families of porous materials studied for this purpose in the near future.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%
“…Such an approach has been used previously for C 60 in combination with other small molecules, such as hydrogen, 17 water, 18,19 ammonia 20 and carbon dioxide. 21 The electron ionization of pure methanol clusters in helium nanodroplets has been reported previously. 22,23 In the most recent study cluster ions containing up to 100 methanol monomers were observed.…”
Section: Introductionmentioning
confidence: 99%
“…We can relate our results to ordering in molecular adsorbates of nonpolar molecules on fullerene C 60 . These systems are still actively researched to this date [64][65][66][67] and represent a spherical analogue of the 2D adsorption cases where quadrupolar interaction between molecules was shown to dictate the orientational order. If quadrupolar moments of adsorbed molecules are high enough (as is the case for H 2 , N 2 and ethylene), the positional order of quadrupoles can become commensurate with the underlying lattice.…”
Section: Resultsmentioning
confidence: 99%
“…In many real systems, quadrupoles are not free to rotate but are rather constrained around some preferred tilt, dictated by the interaction with the substrate as well as temperature. 66,71 Additionally, quadrupole eigentensors can differ from the rotationally symmetric linear type. We examine the dependence of the ground state configuration on the parameter a that determines the quadrupolar eigenvalues, at different fixed inclinations y between the surface normal and the eigenvector corresponding to the highest eigenvalue e 1 = 2 +a.…”
Section: Constrained Solutions and Different Quadrupole Tensorsmentioning
confidence: 99%